Pengaruh Digital Marketing terhadap Keputusan Pembelian Konsumen pada UMKM Kuliner di Palembang - Vania Gitta Khansa Putri; Yohanes Ferry Cahaya (Jurnal Ekonomi dan Bisnis Digital, 2026)
The advancement of digital technology has transformed consumer buying and selling behavior. Micro, Small, and Medium The development of digital technology has brought changes to marketing patterns and consumer purchasing behavior, including in the food Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the influence of digital marketing on food MSME purchasing decisions in Palembang City. This research uses a quantitative approach with a survey method through the distribution of questionnaires to 100 respondents who have purchased food MSME products through digital media. The research instrument used a Likert scale, and the data were analyzed using descriptive analysis, validity testing, reliability testing, correlation analysis, and ANOVA testing. The results showed that the digital marketing variable obtained an average score of 3.77, categorized as good, while the purchasing decision variable obtained an average score of 3.78, categorized as good. The correlation test results indicated a positive and strong relationship between digital marketing and purchasing decisions, with a Pearson Correlation value of 0.866 and a significance level of 0.000. The ANOVA test results also showed that digital marketing had a significant effect on purchasing decisions, with an F value of 318.439 and a significance level of 0.000. The findings indicate that the ease of finding social media accounts, fast admin responses, product information availability, and digital promotions are factors that support consumers in making purchasing decisions. Therefore, implementing an effective digital marketing strategy can increase product attractiveness, consumer trust, and repurchase opportunities for food MSMEs in Palembang City.